2010
DOI: 10.1002/pssc.200983629
|View full text |Cite
|
Sign up to set email alerts
|

Carrier injection in InAlGaN single and multi‐quantum‐well ultraviolet light emitting diodes

Abstract: 316 nm (In)AlGaN light emitting diodes (LEDs) with one, three, five and seven quantum wells (QWs) have been investigated. The carrier injection in the devices is simulated and compared with electroluminescence measurements. The emission power of all LEDs is nearly the same at low currents. This effect is attributed to the inhomogeneous carrier distribution in the QWs of the multi‐quantum‐well (MQW) structures. Only the first two QWs closest to the p‐side of the diode contribute significantly to the optical emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The design of the EBL is critical to prevent electron leakage from the quantum well active region into the p-doped layers of the LED and to provide efficient hole injection into the active region. [4][5][6] EBLs for UV-B and UV-C LEDs require p-doped Al x Ga 1Àx N layers with a typical thickness of around 20 nm and an aluminum content x of more than 75%. [7][8][9] Because of the very high activation energy of the magnesium acceptors in such high aluminum mole fraction layers, 10,11 it is very challenging to realize conductive p-doped AlGaN:Mg EBLs.…”
mentioning
confidence: 99%
“…The design of the EBL is critical to prevent electron leakage from the quantum well active region into the p-doped layers of the LED and to provide efficient hole injection into the active region. [4][5][6] EBLs for UV-B and UV-C LEDs require p-doped Al x Ga 1Àx N layers with a typical thickness of around 20 nm and an aluminum content x of more than 75%. [7][8][9] Because of the very high activation energy of the magnesium acceptors in such high aluminum mole fraction layers, 10,11 it is very challenging to realize conductive p-doped AlGaN:Mg EBLs.…”
mentioning
confidence: 99%
“…The optimization of the current spreading layers, the active region, the electron blocking layer (EBL), and the contact layers is very important to improve the power and operating voltage of UV LEDs. We have previously extensively discussed the influence of the n‐layer heterostructure design, [ 12 ] the quantum‐well (QW) and quantum‐barrier composition, [ 13 ] the QW numbers, [ 14 ] and the QW width [ 15 ] as well as the EBL design [ 16,17 ] on the emission characteristics and efficiency of UV LEDs. The p‐layer heterostructure design and the p‐doped cap layer are further key challenges to realize efficient UV LEDs with a low operating voltage.…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier publications we have discussed the influence of the QW barrier composition on the emission characteristics of near UV LEDs 1, 2. An additional study is related to the number of QWs in 316 nm LEDs 3. Hirayama et al 4, 5 reported that the optimum QW thickness for UV LEDs is roughly between 1.5 and 2.5 nm.…”
Section: Introductionmentioning
confidence: 99%